2018
DOI: 10.1038/s41598-018-32138-2
|View full text |Cite
|
Sign up to set email alerts
|

Morroniside regulates hair growth and cycle transition via activation of the Wnt/β-catenin signaling pathway

Abstract: Hair loss is characterized by a shortened hair anagen phase and hair follicles (HF) miniaturization. Morroniside is the most abundant iridoid glycoside extracted from Cornus officinalis and has various bioactivities in different cell functions and tissue regeneration. In this study, we investigated the effects and the underlying mechanism of morroniside on hair growth and regulation of HF cycle transition. Morroniside treatment significantly enhanced outer root sheath cell (ORSC) proliferation and migration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…The results showed that the expression of β-catenin and p-Erk 1/2 in the DP spheroid groups was up-regulated, and that of SFRP2 was down-regulated in comparison to the control and minoxidil groups. The WNT/β-catenin pathway has a critical role in regulating the hair cycle by promoting hair growth ( 35 ). β-Catenin is a key regulator of hair follicle growth, and it is reported to be the primary initiator of the anagen phase ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the expression of β-catenin and p-Erk 1/2 in the DP spheroid groups was up-regulated, and that of SFRP2 was down-regulated in comparison to the control and minoxidil groups. The WNT/β-catenin pathway has a critical role in regulating the hair cycle by promoting hair growth ( 35 ). β-Catenin is a key regulator of hair follicle growth, and it is reported to be the primary initiator of the anagen phase ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…To understand the hair-inducing property of hFB-EVs, we also treated ORS cells with hFB-EVs. Migration and proliferation of ORS cells contributed to the outgrowth of ORS cells and HF [39,40]. ORS cells have been involved in the migration of hair stem cells to hair bulb for facilitating HF elongation [41].…”
Section: Discussionmentioning
confidence: 99%
“…Injection of morroniside (100 µM) in depilated mouse skin increased the skin thickness and immunohistochemical analysis revealed the elevated expression of β-catenin in epidermis, outer root sheath cells, and matrix during telogen–anagen transition. The compound markedly reduced catagen entry as compared to control [ 72 ]. Several other plant extracts, such as extracts of polygonum multiflorum [ 73 ], Aconitie ciliare tuber [ 75 ], Thuja orientalis [ 76 ], Malva verticilata [ 77 ], and rice bran extract [ 79 ], have been reported to promote mouse skin hair growth or the proliferation of human DPCs via the activation of β-catenin signaling.…”
Section: Progress In Developing Therapy For Hair Loss By Targetingmentioning
confidence: 99%